2015
DOI: 10.1038/srep11353
|View full text |Cite
|
Sign up to set email alerts
|

Reassortment and distinct evolutionary dynamics of Rift Valley Fever virus genomic segments

Abstract: Rift Valley Fever virus (RVFV) is a member of Bunyaviridae family that causes a febrile disease affecting mainly ruminants and occasionally humans in Africa, with symptoms that range from mid to severe. RVFV has a tri-segmented ssRNA genome that permits reassortment and could generate more virulent strains. In this study, we reveal the importance of reassortment for RVFV evolution using viral gene genealogy inference and phylodynamics. We uncovered seven events of reassortment that originated RVFV lineages wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
6
23
0
Order By: Relevance
“…Interestingly, Freire et al . [33] found a lower evolutionary rate in the large minigenomic segment, suggesting a distinct evolutionary history in the three segments; our results corroborated this finding [33]. …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Interestingly, Freire et al . [33] found a lower evolutionary rate in the large minigenomic segment, suggesting a distinct evolutionary history in the three segments; our results corroborated this finding [33]. …”
Section: Discussionsupporting
confidence: 91%
“…The substitution rate estimates in our study were similar to those in previous studies [33,43]. Other studies have reported higher rates [32,44]: for example, estimates from Aradaib et al .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations